The Effect Of Servant Leadership And Person-Organization Fit On Job Satisfaction Mediated By Motivation (Study on OPD Employees in Batang District) - Mutrofin; Lie Liana (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of servant leadership and person-organization fit on job satisfaction mediated by motivation. This study uses a quantitative research approach with a population of 67 ASN employees in the Batang District OPD. Data were processed using SPSS software version 24. Data analysis techniques include respondent descriptions, variable descriptions, validity tests, reliability tests, F tests, R2 tests, t tests, and Sobel Tests. The results of the study state that servant leadership has a positive effect on motivation, person-organization fit does not affect motivation, servant leadership has a positive effect on job satisfaction, person-organization fit does not affect job satisfaction, motivation has a positive effect on job satisfaction, motivation mediates the effect of servant leadership on job satisfaction, and motivation does not mediate the effect of person-organization fit on job satisfaction